Business associations in Benin “at work” The paradoxes of private sector development - BADOU, AGNES OLADOUN; Bierschenk, Thomas (My University, 2021)
Addressing the expectation of development researchers and practitioners that strong business associations are of particular importance for economic development, this paper analyses the real workings of these associations, using the example of the Republic of Benin. In this country, large organizations function in a deeply-politicized milieu, with the government trying to control them through a policy of divide and rule as well as political cooptation in order to generate party political support and minimize opposition. The large business associations are thus actors in regime politics rather than representatives of an autonomous capitalist class, in line with a historical tradition of successive governments trying to capture and control the private sector. At the same time, the smaller associations are often closely interwoven with the social arena of international development policy. However, the promotion of smaller associations by development agencies cannot prevent them from being politicized. The paradoxical effect of this is that private sector development policy weakens rather than strengthens the private sector, and that a commitment to slogans like private sector development offers the opportunity for local actors to look for new forms of rent-seeking. The Beninese variant of rentier capitalism remains highly subservient to the political regime.
Keywords: capitalism; private sector; business associations; class; development